Comparative survey of profitability, production and sustainability between organic and conventional farming (case study on corn, rice and tomato farmers in Minahasa) - Rumondor, Fadly Steven Jefry (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2025)
This study aimed to bridge the knowledge gap by comparing productivity (yield), profitability (profit margin per hectare), and sustainability index between organic and conventional systems. This study applied a comparative observational design with two treatment groups: organic and conventional farming. Population observed in this study was farmers cultivating rice, corn, and tomatoes in the study area. Sampling was carried out using stratified random sampling based on crop type, ensuring balanced representation across the two farming systems. The sample size was 100 plots per system, resulting in 200 plots. Assumptions of normality and homogeneity of variances were tested using the Shapiro–Wilk and Levene's tests, respectively. Independent samples t-tests were conducted at α = 0.05 to compare yield, profit margin, and sustainability index between systems. A two-way ANOVA was performed if a system × crop interaction was significant. Power Analysis via Monte Carlo Simulation was performed to ensure the study has sufficient statistical power (≥ 0.80) to detect the expected differences in yield, profit margin, and sustainability index between organic and conventional systems. Organic farming demonstrates robust advantages in profit and sustainability, with promising but variable impacts on yield. Researchers and policymakers should prioritize adequately powered studies when comparing agronomic performance to ensure that subtle yield effects are not overlooked.